Improving the professional competense in training futurecompyuter science teachers - Mukhamadieva Feruza Eshnazarovna (Research Parks Publishing LLC, 2021)
This article discusses improving the quality of education, the task of forming and developing the competence of a computer science teacher, the goals of introducing a teaching standard aimed at improving the qualifications of teachers, and developing computational thinking